“ENEMY OF MY ENEMY IS MY FRIEND” REUNITING ISLAM DAN CULTURE IN INDONESIAN HORROR MOVIE - Zulkifli Makmur (International Conference on Social and Islamic Studies, 2021)
Culture, in Indonesia, is positioned under Islamic discourse. It commonly sense happens inIndonesian horror movies, including Beranak dalam Kubur dan Bernafas dalam Lumpur. Bernafasdalam Kubur (2018), a horror movie adapting both movies, designs Islamic discourse and culturemore equally. The article works by Derrida’s deconstruction concept. Data collection is taken fromscenes of Bernafas dalam Kubur (2018). It is taken from Beranak dalam Kubur and Bernafas dalamLumpur if needed. It finds that Sundal Bolong is cultural discourse image of Nusantara which existsas humanism tool against inhumanism. The article, in addition, finds that Sundal Bolong explicitlycan collaborate with Islamic thought against evil.